Comecon as the «Core» of Alternative Globalization - A. A. Popov (MGIMO University Press, 2021)
Book review: «The World System of Socialism» and the Global Economy in the mid-1950s – mid-1970s/ ed. by M.A. Lipkin. Moscow: Ves’ mir, 2019.